Comparison of Medical and Consumer Wireless EEG Systems for Use in Clinical Trials - Ratti, Elena; Waninger, Shani; Berka, Chris; Ruffini, Giulio; Verma, Ajay (Frontiers in Human Neuroscience, 2017)
Objectives: To compare quantitative EEG signal and test-retest reliability of medical grade and consumer EEG systems. Methods: Resting state EEG was acquired by two medical grade (B-Alert, Enobio) and two consumer (Muse, Mindwave) EEG systems in 5 healthy subjects during two study visits. EEG patterns, power spectral densities (PSDs) and test/retest reliability in eyes closed and eyes open conditions were compared across the four systems, focusing on Fp1, the only common electrode. Fp1 PSDs were obtained using Welch’s modified periodogram method and averaged for the five subjects for each visit. The test/retest results were calculated as a ratio of Visit 1/Visit 2 Fp1 channel PSD at each one second epoch. Results: B-Alert, Enobio and Mindwave Fp1 power spectra were similar. Muse showed a broadband increase in power spectra and the highest relative variation across test-retest acquisitions. Consumer systems were more prone to artifact due to eye blinks and muscle movement in the frontal region. Conclusions: EEG data can be successfully collected from all four systems tested. Although there was slightly more time required for application, medical systems offer clear advantages in data quality, reliability and depth of analysis over the consumer systems. Significance: This evaluation provides evidence for informed selection of EEG systems appropriate for clinical trials.